An Unusual Case of Bilateral Empyema Associated with Bee Sting - Srinivasa Kaligonahalli Venkataramanappa; Amban Gowda; Srinivas Raju; Vijeth Harihar (Case Reports in Medicine)
Bee sting in most situations is life threatening. Spectrum of bee sting ranges from mild local reaction to death. The literature regarding the bee sting disease from India is sparse. The rare manifestations of the disease include encephalitis, polyneuritis, myocardial infarction, pulmonary edema, bleeding manifestations, and renal failure. Bee sting infections are rare and no field studies have been performed to determine the exact sequence of events that lead to infection of bee stings and if not treated properly can lead to fatal outcomes. Here we present a case of unusual bilateral empyema associated with bee sting.